Concentraciones de hongos en el aire alrededor del relleno sanitario modelo Callao - Rios Valle, Diana Isabel (2025)
Non-hazardous waste generated in Metropolitan Lima and Callao is transported to the Modelo Callao landfill for safe disposal. The accumulation of waste constitutes a significant source of fungal particles released into the atmosphere, posing a potential health risk to nearby populations. The aim of this research was to evaluate the concentration of outdoor fungal particles, considering environmental conditions (temperature, relative humidity, wind speed, and direction) during summer and winter seasons in the 18 de octubre settlement and Chill´on Avenue, areas located in the vicinity of the Modelo Callao Landfill in Ventanilla during 2022. The gravitational method was used for sampling. The highest concentrations were detected at 150 and 200 m from the landfill, where a kindergarten and a local park are located. Fifteen fungal genera were identified in both seasons. The predominant fungi were Aspergillus spp. (46.09 %), Penicillium spp. (23.29 %) and Alternaria spp. (11.33 %). The average concentrations during summer and winter were 297.21 CFU/m3 and 471.69 CFU/m3, respectively. Based on these findings, we recommend that residential areas be located beyond 200 m from the landfill to minimize exposure to fungal aerosols. Additionally, we propose the implementation of an action plan to improve air quality in the areas surrounding the final disposal infrastructure.